2015
DOI: 10.1007/s00417-015-3111-2
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the effect of under-correcting myopia

Abstract: The Letter to the Editor BRefractive correction and myopia progression^[1] (Bthe Letter^) makes some good points about the article BThe progression of corrected myopia^ [2] that the article had already addressed in part.Medina's feedback model for emmetropization predicts that correction of myopes aggravates their condition, and that delaying correction will result in less progression rate and probably a reduced myopic final level. The model also predicts that under-correcting myopia would have a small effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Atropine users are therefore uncorrected, under corrected, or plus corrected during near vision. In either case, feedback theory predicts a reduction in the progression rate of myopia, as several investigators confirmed [25][26][27]. Chia et al results [23] also support the feedback theory explanation for the reduced progression rate.…”
Section: Resultsmentioning
confidence: 84%
“…Atropine users are therefore uncorrected, under corrected, or plus corrected during near vision. In either case, feedback theory predicts a reduction in the progression rate of myopia, as several investigators confirmed [25][26][27]. Chia et al results [23] also support the feedback theory explanation for the reduced progression rate.…”
Section: Resultsmentioning
confidence: 84%
“…As previously discussed by Medina 2016 [ 20 ], most studies until now have used different groups of subjects (treatment vs. control). In contrast, the authors proposed to use the same subjects before and after the subjects received their full prescription.…”
Section: Study Protocolmentioning
confidence: 99%
“…It is clear that these two opinions will not be resolved in the immediate future by experiment, theory, or practice. The normal approach used in the fact of disputed evidence and unresolved opinions is to explain both approaches to the individualallowing him to make the inal decision regarding the use of myopia avoidance techniques [1][2][3][4][14][15][16][17]29].…”
Section: Changing the Environment With A Lensmentioning
confidence: 99%
“…Hung & Ciuffreda [11], develop IRDT, incremental retinal defocus, to explain myopia during the growth phase. Medina et al [12][13][14] and Greene & Medina [15][16][17][18], use control theory to explain myopia development, solved with digital and analog computer techniques to evaluate irst-order equations. Viikari [19] and Goldschmidt [20], present comprehensive reviews of juvenile myopia, and various techniques used to control this myopia progression.…”
Section: Introductionmentioning
confidence: 99%